The new Canadian Model investment treaty: A quiet evolution - Charles-Emmanuel Côté (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2022)
Canada published its new model investment agreement in 2021, a first substantial revision since the publication of the 2004 model. This new model marks a quiet evolution, integrating useful innovations found in latest treaty practice, but proposing few original solutions. The main innovations that it introduces are a most welcomed expedited arbitration procedure, and a laudable but disappointing section on investment facilitation.
Keywords: 330